Experiências trans femininas/trans masculinas e travestis: arranjos e estratégias para vidas vivíveis na cidade de Campo Grande-MS - ADRIANA CRISTIANE LOPES LINO (2021)
This dissertation is the result of a qualitative research with an ethnographic bias. Throughout the investigation, attention was paid to the memories of six trans women / trans men and transvestites in the city of Campo Grande (MS). The aim was to identify, identify and analyze how their trans performativities were constituted in tension and negotiation with hegemonic heterocisnormative representation systems. Focusing on the facts that marked the processes of recognition of their self-perceived gender identities, their arrangements and strategies were highlighted as ways of articulating their gender performances in their journeys. Therefore, the concepts of identity and experiences become fundamental as they need to be taken into account in this process of reframing. This research triggered differentiation categories that articulate with gender and sexuality for analysis, through an intersectional approach, as the social markers of difference can function as bodily, affective and social arrangements and strategies in the life of materials in the construction and recognition of their identities, according to the need for interaction of the interpellations suffered. From a theoretical and methodological point of view, this dialogue took place in an interdisciplinary way based on Cultural Studies, feminist criticism, transfeminist theory and through queer analytics. Keywords: Trans people. Arrangements. Strategies. Identity. Experiences. Memoirs. Performativity. Crossings.